Cellulosic ethanol production: Landscape scale net carbon strongly affected by forest decision making. (December 2015) - Brunner, Anna; Currie, William S.; Miller, Shelie
Abstract: In producing cellulosic ethanol as a renewable biofuel from forest biomass, a tradeoff exists between the displacement of fossil fuel carbon (C) emissions by biofuels and the high rates of C storage in aggrading forest stands. To assess this tradeoff, the landscape area affected by feedstock harvest must be considered, which depends on numerous factors including forest productivity, the amount of forest in a fragmented landscape, and the willingness of forest landowners to sell timber as a bioenergy feedstock. We studied landscape scale net C balance by combining these considerations in a new, basic simulation model, CEBRAM, and applying it to a hypothetical landscape of short-rotation aspen forests in northern Michigan, USA. The model was parameterized for forest species, growth and ecosystem C storage, as well as landscape spatial patterns of forest cover in this region. To understand and parameterize forest owner decision making we surveyed 505 nonindustrial private forest (NIPF) owners in Michigan. Survey results indicated that 47% of these NIPF owners would willingly harvest forest biomass for bioenergy. Model results showed that at this rate the net C balance was 0.024 kg/m 2 for a cellulosic ethanol system without considering land use over a 40 year time horizon. When C storage in aggrading, nonparticipating NIPF land was included, net C balance was 1.09 kg/m 2 over 40 years. In this region, greater overall C gains can be realized through aspen forest aggradation than through the displacement of gasoline by cellulosic ethanol produced from forest biomass. Highlights: We survey non industrial private forest owners in Michigan. We create and apply a new model of carbon accounting for bioenergy in Michigan. 47% of forest landowners would harvest trees as a bioenergy feedstock. Cellulosic ethanol production has a small positive carbon balance. Forest growth with no harvest has a much greater positive carbon balance.